ChemInform Abstract: Solid‐Supported Rhodium(0) Nano‐/Microparticles: An Efficient Ligand‐Free Heterogeneous Catalyst for Microwave‐Assisted Suzuki—Miyaura Cross‐Coupling Reaction. Issue 15 (25th March 2013) - Guha, Nitul Ranjan; Reddy, Chennayala Bal; Aggarwal, Nidhi; Sharma, Dharminder; Shil, Arun K.; Bandna, Bandna; Das, Pralay
Abstract Newly synthesized solid‐supported rhodium nanoparticles are applied in Suzuki—Miyaura cross‐coupling reactions with various aryl halides.